1990
DOI: 10.1002/pen.760300904
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and processing of blends of polyethylene terephthalate with several liquid crystalline polymers

Abstract: Blends of an engineering thermoplastic, poly(ethylene terephthalate) (PET), and two liquid crystalline polymers (LCPs) viz., copolyesters of PET and parahydrox‐ybenzoic acid (PHB) in 40/60 mole percent (LCP60) and in 20/80 mole percent (LCP80) were prepared. A blend of LCP60 and LCP80 in 50/50 weight percent (LCP60‐80) was blended with PET. Both flat films and rods were extruded and their properties examined. The morphology of the films investigated using Scanning Electron Microscopy (SEM) revealed that the LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(36 citation statements)
references
References 18 publications
3
33
0
Order By: Relevance
“…It is clear that the addition of CB nanoparticles largely accelerates crystallization from the t 1/2 values of neat PET and CB/PET composites in Table 3. It is reported that the crystallization rate increases by the addition of polymeric nucleating agents [18][19][20][21][22][23][24][25][26][27]. The results in the present work also indicate that CB nanoparticles may be an ideal nucleating agent for PET crystallization processing.…”
Section: Isothermal Crystallization Kineticssupporting
confidence: 72%
“…It is clear that the addition of CB nanoparticles largely accelerates crystallization from the t 1/2 values of neat PET and CB/PET composites in Table 3. It is reported that the crystallization rate increases by the addition of polymeric nucleating agents [18][19][20][21][22][23][24][25][26][27]. The results in the present work also indicate that CB nanoparticles may be an ideal nucleating agent for PET crystallization processing.…”
Section: Isothermal Crystallization Kineticssupporting
confidence: 72%
“…We note that the process of forming an elongated thermotropic PLC fibrous structure in-situ depends on factors such as the relative composition, the interfacial tension, the viscosity ratio, and the flow field involved in the processing procedure [23]. We note that the process of forming an elongated thermotropic PLC fibrous structure in-situ depends on factors such as the relative composition, the interfacial tension, the viscosity ratio, and the flow field involved in the processing procedure [23].…”
Section: Polyester and Plc Blendsmentioning
confidence: 89%
“…The resulting ''molecular composite'' can be regarded as a material in which the rigid crystalline polymers are reinforced at a molecular level. Liquid crystalline polymer blends have been reported for PC [129], [130]; PEI [129]; PP [131]; PBT [132]; PPE -PS [133]; ABS [134]; PSU [135]; PETP [136], [137]; and PA 6 [138]. These blends can be processed by conventional techniques such as extrusion, injection molding, and fiber spinning.…”
Section: New Developmentsmentioning
confidence: 99%